Antimicrobial activity of tigecycline against methicillin resistant Staphylococcus aureus in a tertiary care setting - Sattar, Abdul; Abbasi, Shahid Ahmad; Faqir, Farah; Mirza, Irfan Ali; Usman, Javaid; Faraz, Ali (Pakistan Armed Forces Medical Journal, 2011)
Objective: To determine the in vitro efficacy of tigecycline against methicillin resistant Staphylococcus aureus (MRSA). Place and Duration of study: Department of Microbiology Army Medical College and Armed Forces Institute of Pathology Rawalpindi, from Feb 2008 to Jan 2009. Materials and Methods: One hundred clinical isolates of MRSA were taken. Detection of MRSA was done using 30µg disc of cefoxitin as recommended by Clinical laboratory Standard Institute (CLSI). Susceptibility of the isolates to tigecycline was done by employing modified Kirby Bauer disk diffusion technique, according to the guidelines provided by the Food and Drug Administration (FDA). Minimum inhibitory concentrations (MICs) of the isolates were determined by using E-strips (bioMerieux) of tigecycline. Results were interpreted according to FDA recommendations. Results: All MRSA isolates were susceptible to tigecycline by disc diffusion method. The MICs of tigecycline revealed that all MRSA isolates were in sensitive range. Conclusion: In an era of rapidly growing antibiotic resistance, tigecycline has been found to have very good in vitro efficacy against MRSA isolates.